Influence of sociocultural beliefs and practices on contraception in Deli Serdang, Indonesia - Gustina, Jessi; Apriani, Riny; Syahna, Syahfira Ananda; Nurhaida, Nurhaida (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Family planning (KB) is one of the government programs to control the rate of population growth. This Program is aimed to improve the welfare of the people of Indonesia and support the Sustainable Development Goals (SDGs) development system. Implant is one type of long-term hormonal contraception that has proven to be very effective in preventing pregnancy for three to five years. With a success rate of 97 to 99%, the implant is a very effective contraceptive method for women of childbearing age who want to delay or prevent pregnancy. However, the level of use of implants among the public is still relatively low. Purpose: To determine the relationship of trust and socio-cultural couples of childbearing age in the use of use of an intrauterine device under the skin (AKBK). Methods: A descriptive quantitative approach, specially focusing on cross-sectional method. The study took place from March 2025 in Clinic Yanti Bandar Setia, Deli Serdang. The independent variable was trust and sociocultural, dependent variable is use of contraceptives under the skin. Using accidental sampling and slovin formula, 31 respondents were selected who met specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using chi-square test. Results: The results of chi-square analysis showed that there was a significant correlation between trust (p=0.003) and social culture (p=0.005) with the use of IMR in fertile couples. Conclusion: The level of trust and socio-cultural factors have a significant effect on the decision of couples of childbearing age to use implantable contraceptives.